Terrestrial frogs of the genus Pristimantis (Anura: Craugastoridae) from the River Zúñag Ecological Reserve, Tungurahua, Ecuador: Annotated list and description of a new species - Marco M. Reyes-Puig; Juan Pablo Reyes-Puig; Mario H. Yánez-Muñoz (ACI Avances en Ciencias e Ingenierías, 2013)
We present a synopsis of 17 species of the genus Pristimantis recorded at the Río Zuñag Ecological Reserve. This reserve is located at the upper Pastaza river basin, on the Cordillera Oriental of the Andes of Ecuador, between 1400 and 2200 m elevation. We include the description of a new species of Pristimantis characterized by its dorsal colouration in life (ambar yellow dorsum with reddish-brown marks, and orange-yellow spots on the groin and posterior surfaces of the thighs) and by the presence of two small tubercles on the upper eyelid and one small interorbital tubercle. We estimate that within the altitudinal range of the reserve may occur 23 species of Pristimantis, divided into two assamblages that get apparently separated at 1800 m elevation.